Peran dzikir dalam mengurangi tingkat kecemasan pada mahasiswa - Mustofa, Muhammad Royhan (Maliki Interdisciplinary Journal, 2026)
Anxiety is a common psychological problem among university students due to academic and social pressures. This article aims to examine the role of dhikr in reducing anxiety levels in students through a literature review of previous studies. The results show that dhikr plays a significant role in reducing anxiety through relaxation mechanisms, increased self-control, and fostering inner peace. Consistent dhikr practice can reduce stress hormones, calm the mind, and strengthen spiritual connection with Allah SWT. Research proves that high intensity of dhikr correlates with low anxiety levels and increased psychological well-being of students. Dhikr can be recommended as an effective spiritual-based psychological intervention that aligns with Islamic values.